(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Disability literature has been embellished with exhilarating portrayal of individuals who are vanquishing their physical and societal barriers to effectuate antecedence in life. However, some unprecedented set of stories elucidates an illustrious anomaly of maimed luminary amassing laugher without any tangential assistance. The present study ransacks into the gumption and audacity of self-reliant protagonists Rowthore and Mr. Parson who reconnoiter their peerless journeys and the profound impact of their depiction in disability literature. Despite the striking differences between the nationalities of the authors, genre, culture and the historical period, Sundara Ramaswamy’s “Reflowering” and Mackinlay Kantor’s “A Man who had no eyes” have unsung protagonists, who have tenacity, fortitude and zeal towards their profession. The study accentuates the self-empowerment of the protagonists, who galvanizes us a deeper appreciation for their human spirits beyond their limitations.